DIFFICULTIES IN TEACHING FOREIGN LANGUAGES TO YOUNG LEARNERS - Xoshimova Nilufar; Jalolova Muqaddas (TADQIQOTLAR, 2025)
Abstract Teaching foreign languages to young learners is both a rewarding and challenging task. While children have a natural ability to acquire new languages, the teaching process involves several difficulties. This article explores the common challenges faced by language teachers when working with young learners and provides insights into how these issues can be addressed effectively.